Некоторые проблемы защиты права собственности при применении мер уголовно-процессуального принуждения - Kirillova, Nataliya (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the relation between right to property and the criminal procedure compulsions. The author presents the selected issues of the property right protection law system in the context of the criminal proceeding.